Morphological and anatomical study and quantitative determination of polysaccharides in fruits, pericarp and seeds of Elettaria cardamomum L. - Soltyk, Olga; Makhinya , Larysa (The Ukrainian Scientific Medical Youth Journal, 2025)
cardamomum is officially included in the Pharmacopoeias of India, United Kingdom, and United States of America. In our country, it is a spice and is not used for medical purposes. The study of the macro- and microscopic structure of fruits and seeds, as well as chemical components, in particular polysaccharides, will allow developing methods for quality control of raw materials for fruits with E. cardamomum seeds. This approach will expand the use of herbal preparations with cardamom in Ukraine. In addition, it will ensure the waste-free use of cardamom in the medical, pharmaceutical and food industries, since only seeds rich in volatile essential oils are used for industrial purposes, and the pericarp is utilized. The article analyzes the current literature data on the phytochemical composition, use in pharmacy and medicine of E. cardamomum. The main morphometric features of E. cardamomum fruits and seeds, which play a key role in the identification of the species, have been established. The anatomical features of fruits and seeds of E. cardamomum were studied under light and electron microscopes, a number of micromorphological features were revealed, in particular, idioblasts with essential oil, angular layer, waxy scales on the surface of seeds. Quantitative determination of polysaccharides in seeds, fruits and pericarp of E. cardamomum was carried out. The highest content of polysaccharides was found in the pericarp - 4.7%, the average in the fruit - 2.8% and the lowest in the seeds - 2.22%.